The Effect of Discipline and Work Motivation on Work Productivity on Shaza Depok Employees - Putri Nilam Kencana; Lia Asmalah; Baliyah Munadjat (Kusuma Negara Business School, 2021)
The purpose of this study was to determine the effect of discipline and work motivation on employee productivity at PT. SHAZA Depok. The population in this study were all employees, totaling 60 employees and in conducting this research used research methods (1). Types of research are library research and field research. (2). data collection techniques, namely observation, documentation, questionnaires, interviews. (3). Quantitative analysis tools using the SPSS 18 for Windows program. The Result of this study is Work discipline (X1) and work motivation (X2) simultaneously affect work productivity.